Pembuatan Kompos Menggunakan Komposter Ember Tumpuk di Desa Salo Cella - Ahmad Moh Nur; Syaipurahman Syaipurahman; Muhammad Dwiki Surya Saputra; Rafly Genta Pratama; Anugrah Dimas Firzatullah; Mita Wahyu Astami; Agusfoni Zalukhu; Firdhanur Aulia Putri; Arima Widya Putri; Anita Nur Arfyani; Fina Anriani (Jurnal Pengabdian Kepada Masyarakat, 2025)
Kuliah Kerja Nyata (KKN) Bina Desa of Mulawarman University in Salo Cella Village, Muara Badak District, Kutai Kartanegara Regency, aimed to provide a solution for organic waste management through the use of a stacked bucket composter system. The village does not yet have a Temporary Waste Disposal Site (TPS), resulting in waste often being burned or dumped into the river, causing pollution. The stacked bucket composter method was chosen because it is simple, affordable, easy to apply at the household level, and capable of producing two products: solid compost as a planting medium and liquid organic fertilizer (POC) as plant nutrients. The process involved chopping organic waste, mixing it with rice husk ash, and adding an EM4 and molasses solution to accelerate decomposition. The results indicated enthusiasm from the residents, particularly in RT 01, for applying this technology as an effort to reduce organic waste volume and increase environmental awareness. This program is expected to be replicated through community outreach and empowerment to establish sustainable waste management in Salo Cella Village.